2021
DOI: 10.1016/j.clnu.2020.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of phenolic compounds to reduce intestinal damage and improve the intestinal barrier integrity: A systematic review of in vivo animal studies

Abstract: Background & aims: The integrity of the intestinal barrier in the diseased is key to prevent further complications and disease such as sepsis and death, whereas, the role of food bioactive molecules (i. e. phenolic compounds (PCs) on the intestinal barrier, is still unknown. The current aim was to explore the benefits of the oral PC administration on the intestinal barrier integrity in animals. Methods: The effects of PCs on the intestinal barrier integrity in in vivo animal models of intestinal inflammation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 61 publications
(162 reference statements)
2
17
0
Order By: Relevance
“…IL-10 is a necessary inflammatory factor for inducement and maintenance of regulatory T (Treg) cells against colitis ( Sivaprakasam et al, 2016 ). Numerous plant-extracted polyphenols can decrease the levels of inflammatory cytokines to attenuate inflammation responses ( Sandoval-Ramirez et al, 2021 ). For example, caffeic acid, tea polyphenols, salvianolic acid, and sesamol could ameliorate colitis by reducing the levels of IL-1β, IL-6, TNF-α, and other pro-inflammatory cytokines in DSS-induced models ( Ye et al, 2009 ; Wang et al, 2018 ; Liu et al, 2020b ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a necessary inflammatory factor for inducement and maintenance of regulatory T (Treg) cells against colitis ( Sivaprakasam et al, 2016 ). Numerous plant-extracted polyphenols can decrease the levels of inflammatory cytokines to attenuate inflammation responses ( Sandoval-Ramirez et al, 2021 ). For example, caffeic acid, tea polyphenols, salvianolic acid, and sesamol could ameliorate colitis by reducing the levels of IL-1β, IL-6, TNF-α, and other pro-inflammatory cytokines in DSS-induced models ( Ye et al, 2009 ; Wang et al, 2018 ; Liu et al, 2020b ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory response plays a key role in activating the production of mature IL-6, IL-1β, and TNF-α in UC patients and colitis mice ( Marafini et al, 2019 ). Numerous phenolic acids can inhibit the inflammatory responses to improve colitis ( Sandoval-Ramirez et al, 2021 ). For example, caffeic acid, tea polyphenols, salvianolic acid, and sesamol could ameliorate colitis by reducing the levels of IL-1β, IL-6, TNF-α, and other pro-inflammatory cytokines in DSS-induced colitis mice ( Ye et al, 2009 ; Wang et al, 2018 ; Liu Y. et al, 2020 ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that ELE significantly improved DSS-induced colon epithelial injury and reduced the mRNA expression of TLR4 and IL-6, which might attribute to the enriched phenolic acids, flavonoid, and polysaccharide contents in ELE. Previously, studies have shown that the phenolic acid, total flavonoids, and polysaccharides alleviate IBD by relieving inflammation and oxidative stress ( Zhao et al, 2019 ; Hussain et al, 2020 ; Sandoval-Ramirez et al, 2020 ). Chlorogenic acid, the main component of ELE, showed beneficial effect on ameliorating LPS-induced inflammation in different cell types (i.e., macrophages, hepatocytes, and intestinal cells) by suppressing the TLR4 signaling pathway ( Shi et al, 2013 ; Ruan et al, 2014 ; Ruifeng et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%